Analysis of the risk factors for secondary hemorrhage after abdominal surgery - Pang, Tianshu; Wu, Zhengrong; Zeng, Hongfen; Zhang, Xiangyu; Hu, Mengya; Cao, Liping (Frontiers in Surgery, 2023)
Introduction Our study aims to explore and summarize clinical analysis, providing ideas and references for prevention and treatment of postoperative hemorrhage. Patients and Methods A total of 138 patients after abdominal surgery who underwent postoperative hemorrhage from January 2015 to December 2020 at Sir Run Run Shaw Hospital Affiliated to Zhejiang University School of Medicine were participated in this study. They were divided into single bleeding group and secondary bleeding group, respectively. Univariate and multivariate statistical analysis was performed, then cumulative hazard trends and survival curves were plotted of the two groups. Results Main outcomes of interest with secondary hemorrhage were duration of operation, the first bleeding time, intervention time, combined organ resection, surgical intervention, abdominal infection, admission to intensive care unit (ICU), postoperative length of stay, and total hospitalization expenses. Among them, long operative duration (>5h) and extended intervention time (>5h) were obtained independent predictors for risk of secondary hemorrhage. Conclusions Secondary hemorrhage after abdominal surgery is mainly related to subjective human factors, which is an important cause of poor prognosis and even death. Properly shortening the operation time and quickly responding to treatment of bleeding are the key factors for healing bleeding. Further reduction in postoperative hemorrhage and mortality requires a concerted effort by the surgeons for both intraoperative surgical techniques and postoperative management.